2017
DOI: 10.1111/vde.12488
|View full text |Cite
|
Sign up to set email alerts
|

A novel non‐azole topical treatment reducesMalassezianumbers and associated dermatitis: a short term prospective, randomized, blinded and placebo‐controlled trial in naturally infected dogs

Abstract: Background -Malassezia yeast overgrowth on the skin is a common and often recurrent cause of dermatitis in dogs; it can be an exacerbating factor of atopic dermatitis. Anti-fungal drugs have been a standard treatment, but there is some concern that resistance may be evolving in a spectrum of Malassezia species. Safe, efficient and easy-to-use alternatives are needed.Objectives -To assess if a commercially available topical non-azole solution applied to paws affected by Malassezia-associated dermatitis (MAD), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…With increased recognition of azole resistance in Malassezia species, there has also been an expansion in the investigation of alternative treatment approaches, including photodynamic therapy, natural products, antifungal peptides and proteinase inhibitors [ 443 , 454 , 455 , 456 , 457 , 458 , 459 ].…”
Section: Treatment Of Malassezia -Related Diseasesmentioning
confidence: 99%
“…With increased recognition of azole resistance in Malassezia species, there has also been an expansion in the investigation of alternative treatment approaches, including photodynamic therapy, natural products, antifungal peptides and proteinase inhibitors [ 443 , 454 , 455 , 456 , 457 , 458 , 459 ].…”
Section: Treatment Of Malassezia -Related Diseasesmentioning
confidence: 99%
“…For canine cases where topical therapy is ineffective or impractical, there was "moderate" evidence for the use of ketoconazole at 5-10 mg/kg orally once or twice daily; and itraconazole at 5 mg/kg orally once daily or two consecutive days per week (reviewed by Bond et al, 2020). Recently, the clinical and cytological effects of a once daily application of a leave-on spray formulation containing zinc, ethyl lauroyl arginate, laureth-9, urea, panthenol, glycerine and butylene glycol (Aptus R Derma Spot On Concentrate TM , Orion Pharma Animal Health, Sollentuna, Sweden) were evaluated in a randomized, blinded, controlled study of 18 dogs with chronic pododermatitis associated with Malassezia yeasts (Sjostrom et al, 2018). When compared with placebo treatment of the contralateral foot, reduced yeast counts from the actively treated foot were associated with a reduction in clinical scores.…”
Section: Treatment Of Malassezia Dermatitis In Dogsmentioning
confidence: 99%
“…There is no control group in this study, which is the main limitation of this trial. Nonetheless, some studies on similar clinical conditions with a placebo or a vehicle group, indicated few resolutions in the placebo group compared with the treated group after 2 weeks of application (22,23), even with shampoos where a mechanical effect on microbial count is suspected. Another study, involving an antifungal shampoo vs. a physiologic one showed a significant difference just after one shampoo lasting up to 4 days following the application of the antifungal shampoo whereas no significant difference was observed with the physiologic shampoo (24).…”
Section: Discussionmentioning
confidence: 99%